Impact of the ambient air quality due to the dispersion of non-methane organic compounds from Barka Landfill - Abdul-Wahab, S. A.; Al-Hajri, A.; Yetilmezsoy, K. (SPRINGER, 2016)
This study used the CALPUFF modeling system to study the impact of an area's geophysical and meteorological conditions on the dispersion of non-methane organic compounds (NMOCs) into the atmosphere from the 17-year-old Barka Landfill. Barka Landfill is located in Barka, Batinah, in the north of the Sultanate of Oman. It receives waste from nearby regions such as Nakhal, Seeb, and Wadi Al-Maawel, affecting the town of Barka with landfill gas (LFG) pollution. The present study was conducted to evaluate the impact of the air dispersion of one group of NMOC gases on Barka and the region around it. The top five values of the concentrations with different average time periods, namely 1, 3 and 23 h, were compared with the allowable emission rate defined by the US Environmental Protection Agency (EPA). The results demonstrated that the present integrated modeling system (consisting of a 3D diagnostic CALMET model and Lagrangian puff dispersion CALPUFF model) could be utilized as a useful tool for evaluating the top five peak values of the NMOC emissions of the different time periods.
Keywords: CALPUFF; Dispersion; Landfill; Modeling; Non-methane organic compounds; METEOROLOGICAL CONDITIONS; EMISSION RATES; ODOR; CANADA; MODELS; Environmental Sciences & Ecology